The Phenomenon of Phonological Follow in Al-Amali Abi Ali Al-Qali’s Book (seq.356 Hijri): A Phonological Study: هند فاضل عباس (Journal of the College of Education for Women, 2021)
This research discusses the verbal follow phenomenon in Al-Amali Abi Al-Qali’s book (seq.356 Hijri). It aims to limit the examples of this phenomenon in the book, and examine it phonologically. Accordingly, the researcher adopted the analaytical descriptive approach, taking into account Al-Rawi’s letter when ordering the verbal follow-based examples, and the order they took in the book in question. The purposes behind this phonological study of verbal follow in Al-Amali’s book are to: reach the sounds which Arabs prefer in the process of following, confirm different beautiful and desirable senses, have easy and speedy pronunciation, maintain harmony between adjacent sounds, count the sounds that occur at the beginning of the follower- a disputable phonological issue between the follower and following- and spot the phonological change that occurs to the follower. Accordingly, a caution is needed to maintain harmony and homogeneity between two pronunciations to achieve the process of following. Or, the structure of the word follower is changed to match its peer followed word.The study has shown that Al-Qali was the eldest in dealing with the formal aspect of the phenomenon. He pointed to the idea of merging the last letter in the subordinate and the follower, and compared it with a stylistic, artistic, and acoustic characteristic, which is included in the innate rhetoric, i.e., assonance. By that, he has determined the most important formal acoustic features of the rhythmic complex as represented by the endings of the sequences, which have a musical rhythm.